UPAYA MENINGKATKAN PEMAHAMAN KONSEP IPA MELALUI MODEL PEMBELAJARAN PROBING PROMPTING KELAS III SDN BATUJAYA KOTA TANGERANG - Perdiansyah, Ferry (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2021)
This research is motivated by the problem of low activity and understanding of the concept of science in class III students of SDN Batujaya, Tangerang City. The main problems in this study are: (1) the low interest of students in learning science, (2) the low motivation of students in learning science, (3) students do not develop ideas or ideas, (4) the methods used previously are less precise so students are less enthusiastic in study. This study uses a probing promting model with the aim of: (1) increasing the understanding of the concept of science through the probing learning model for students in class III at SDN Batujaya Kota Tangerang, (2) to find out whether the application of the probing promting learning model can improve the understanding of science concepts of third grade students of SDN Batujaya. This research is a classroom action research with a qualitative approach. In collecting data the author uses several methods, namely: observation method, documentation method, test method. Adapu who is the subject of this research is class III B students with a population of 27 students. The results obtained in each cycle are: in the pre-cycle percentage of students 'understanding of concepts 22.22% who are above the KKM, in cycle 1 an increase in the percentage of students who have grades above the KKM of 64%, in the second cycle the percentage increase in understanding of students' concepts an increase of 83%. This increase occurred because of the maximum use of probing promting learning models conducted by teachers and students so that they are accustomed to using probing prompting learning models in science learning. Keywords : Concept Understanding, Probing Prompting